Microfinance Et Mobilisation De L’epargne Dans Le Secteur Informel. Le Cas Des Commercantes De Vivriers De Bouake - Fofana, Valoua (European Scientific Journal, ESJ, 2017)
In the fight against female poverty, the access to the microfinance services of women in general and those of the informal sector, in particular, is at the center of all the debates in recent years. The dynamics generated by the Institutions of Microfinance, however, have weaknesses, including the mobilization of savings from informal traders who have received financing. This paper aims to shed more light on these problems in a socio-economic approach to the saving behavior of female entrepreneurs. The methodology adopted for this purpose is primarily qualitative and is based on individual interviews and groups carried out with a reasoned sample of 35 respondents. The analysis of the contents of the collected qualitative data made it possible to establish a correlation between the incapacity of the women to save food and a certain number of socio-economic and cultural factors. Although there are beneficiaries of institutional funding, women are generally unable to mobilize formal savings because of, among others things, the amounts of the granted loans, the precarious living conditions, the low level of the incomes, and the rigidity of the system of savings. Generally from underprivileged social categories, these women devote almost all of their modest incomes to family problems. Moreover, the method of collecting the savings developed by microfinance institutions, which consists of moving to an agency for deposits and withdrawals, appears to be constraining and constitutes a factor of demotivation for the members. Faced with these limitations, microfinance institutions are called upon to create more appropriate conditions to encourage the mobilization of formal savings among informal traders.